2000
DOI: 10.1021/jp9919718
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric Oxidation Mechanism of Dimethyl Ether and Methyl Formate

Abstract: The oxidation mechanism of dimethyl ether is investigated using ab initio methods. The structure and energetics of reactants, products, and transition structures are determined for all pathways involved in the oxidation mechanism. The detailed pathways leading to the experimentally observed products of dimethyl ether oxidation are presented. The energetics of over 50 species and transition structures involved in the oxidation process are calculated with G2 and G2(MP2) energies. The principal pathway following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 57 publications
8
85
1
Order By: Relevance
“…They also employed similarities between ethyl acetate and other species to build their detailed kinetic mechanism. Good and Francisco [13] carried out an extensive analysis of methyl formate and dimethyl ether oxidation, using ab initio techniques, to provide kinetic insights into important reaction pathways for methyl formate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…They also employed similarities between ethyl acetate and other species to build their detailed kinetic mechanism. Good and Francisco [13] carried out an extensive analysis of methyl formate and dimethyl ether oxidation, using ab initio techniques, to provide kinetic insights into important reaction pathways for methyl formate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In the most complete study, incorporating a model for collisional stabilization of the radical intermediates, Wang et al 13 used the G2(B3LYP/MP2/CC) method to study the CH 3 O + CO reaction and performed Rice-Ramsperger-Kassel-Markus calculations to predict the products of the multiwell reaction as a function of temperature and pressure. Good et al 5 also published barriers computed at the G2 level of theory for the unimolecular dissociation of the methoxy carbonyl radical but obtained a much lower barrier, 14.7 kcal/mol, to the CH 3 + CO 2 product channel than those predicted by the work of Francisco et al, 1 Kang and Musgrave, 12 Wang et al, 13 and Zhou et al 14 In crossed laser-molecular beam studies of the CH 3 O + CO system, McCunn et al 15 measured product branching ratios under collision-free conditions for the unimolecular dissociation of the CH 3 OCO radical. The experimental results are in dramatic disagreement with predictions using the earlier high barrier calculated for the dissociation of methoxy carbonyl to methyl + CO 2 but in good agreement with the predicted branching ratio using the low barrier height of 14.7 kcal/mol predicted by Good et al 5 for the formation of CH 3 + CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Good et al 5 also published barriers computed at the G2 level of theory for the unimolecular dissociation of the methoxy carbonyl radical but obtained a much lower barrier, 14.7 kcal/mol, to the CH 3 + CO 2 product channel than those predicted by the work of Francisco et al, 1 Kang and Musgrave, 12 Wang et al, 13 and Zhou et al 14 In crossed laser-molecular beam studies of the CH 3 O + CO system, McCunn et al 15 measured product branching ratios under collision-free conditions for the unimolecular dissociation of the CH 3 OCO radical. The experimental results are in dramatic disagreement with predictions using the earlier high barrier calculated for the dissociation of methoxy carbonyl to methyl + CO 2 but in good agreement with the predicted branching ratio using the low barrier height of 14.7 kcal/mol predicted by Good et al 5 for the formation of CH 3 + CO 2 . Subsequent CCSD(T) studies 15 on the unimolecular dissociation of methoxy carbonyl indicated that the lower barrier to the methyl + CO 2 products results from a cis geometry of the transition state (cis-TS), whereas the higher barrier corresponds to a trans conformation at the transition state (trans-TS).…”
Section: Introductionmentioning
confidence: 99%
“…Then about 90% of Intermediate 2 produces CO2 directly through Reaction 3. The 90% value is evaluated at 800K and based on calculated barrier heights for reactions analogous to Reaction 1 and 2 [18]. Reaction path analysis shows that TPGME, whose chemistry leads to mostly aldehydes and CO is a much more optimal molecular structure for an oxygenated fuel based on its potential to reduce soot precursors.…”
Section: Kinetic Model Results and Discussionmentioning
confidence: 99%